Comparison of Ultrasonic Imaging Techniques for Full-Scale Reinforced Concrete. Issue 1 (2016) - Choi, Hajin; Bittner, James; Popovics, John S.
Recent developments in ultrasonic testing hardware, such as air-coupled sensors and multielement shear wave dry-point contact arrays, have brought about a new capability to image the interior of reinforced concrete structures. Data acquired from air-coupled transducers are often reconstructed by using tomographic algorithms, especially when a through-thickness configuration is used to collect data. Data acquired from multielement shear wave arrays are normally reconstructed with the synthetic aperture focusing technique (SAFT), under which the data are collected by using a one-sided pitch-catch configuration. Both approaches are helpful in characterizing full-scale reinforced concrete structures, although each produces a different type of image with distinct characteristics. The differences between the two test methods and data inversion schemes are investigated. Ultrasonic data are collected from a full-scale reinforced concrete column specimen by using air-coupled P-wave transducers and a multielement shear wave array unit. The through-thickness P-wave data are interpreted through tomographic inversion and multielement shear wave data through SAFT reconstructions. The sample column contains embedded artificial defects, including Styrofoam and precracked concrete blocks. The results indicate that both ultrasonic methods produce meaningful internal images with different perspectives. The tomographic reconstructions are insensitive to small cracks and the presence of internal steel bars. The SAFT reconstructions are limited by energy penetration into the structure. On the basis of the comparison study, appropriate applications of ultrasonic imaging tests for each method are suggested.